Synchrony in Learning: Investigating the Connection between Student Adjustment and Academic Performance - Jagneet Kaur; Raino Bhatia (Journal of Research in Education and Pedagogy, 2024)
Adjustment is an important part of human life because it gives people the power and strength to make positive changes in the world around them. The need for adjustment extends beyond the classroom to include classmates, instructors, curriculum, any other school activities and background setting of that place. Those who possess the ability to adapt to the ever-changing conditions in their surroundings have the potential to achieve harmonious living and maintain a contented and well-rounded existence. The present study comprised 191 secondary school students of Sirmaur district, Himachal Pradesh. The method used in the current research was a descriptive survey and stratified random sampling technique was utilized in order to organize and collect data on the basis of gender and locality. The Adjustment Inventory for school students, which was established by A.K.P. Sinha and R.P. Singh and incorporates 60 items evenly split between emotional, social, and educational adjustments, was deployed to measure the level of adjustment of the students. From the previous records, academic scores were taken as academic performance of the students. There is no significant difference of adjustment scores between male and female students of secondary school but highly significant difference (t value 4.376) between urban and rural students. girls are more well-adjusted result shows that rural students are more adjusted than urban students as maximum students of rural area are in good category highly negative correlation between adjustment problems and academic achievement scores of secondary school students.